Associations between environmental pollutants and larval amphibians in wetlands contaminated by energy-related brines are potentially mediated by feeding traits. (May 2019) - Smalling, Kelly L.; Anderson, Chauncey W.; Honeycutt, R. Ken; Cozzarelli, Isabelle M.; Preston, Todd; Hossack, Blake R.
Abstract: Energy production in the Williston Basin, located in the Prairie Pothole Region of central North America, has increased rapidly over the last several decades. Advances in recycling and disposal practices of saline wastewaters (brines) co-produced during energy production have reduced ecological risks, but spills still occur often and legacy practices of releasing brines into the environment caused persistent salinization in many areas. Aside from sodium and chloride, these brines contain elevated concentrations of metals and metalloids (lead, selenium, strontium, antimony and vanadium), ammonium, volatile organic compounds, hydrocarbons, and radionuclides. Amphibians are especially sensitive to chloride and some metals, increasing potential effects in wetlands contaminated by brines. We collected bed sediment and larval amphibians ( Ambystoma mavortium, Lithobates pipiens and Pseudacris maculata ) from wetlands in Montana and North Dakota representing a range of brine contamination history and severity to determine if contamination was associated with metal concentrations in sediments and if metal accumulation in tissues varied by species. In wetland sediments, brine contamination was positively associated with the concentrations of sodium and strontium, both known to occur in oil and gas wastewater, but negatively correlated with mercury. In amphibian tissues, selenium and vanadium were associated with brine contamination. Metal tissue concentrations were higher in tadpoles that graze compared to predatory salamanders; this suggests frequent contact with the sediments could lead to greater ingestion of metal-laden materials. Although many of these metals may not be directly linked with energy development, the potential additive or synergistic effects of exposure along with elevated chloride from brines could have important consequences for aquatic organisms. To effectively manage amphibian populations in wetlands contaminated by saline wastewaters we need a better understanding of how life history traits, species-specific susceptibilities and the physical-chemical properties of metals co-occurring in wetland sediments interact with other stressors like chloride and wetland drying. Graphical abstract: Image 1 Highlights: Metals can co-occur in brines from energy production. Larval amphibians sensitive to wetland salinization from energy development. Metals in sediment and larval amphibians not associated with brine contamination. Larval amphibian grazers had higher concentrations of metals compared to predators. Sediment and aufwuchs source of metal exposure to larval amphibians. Abstract : Metals in wetland sediments were not associated with brines but larval amphibians' feeding traits mediate tissue-metal accumulation in wetlands contaminated by energy-related brines.